ETNOZOOLOGI SEBAGAI MISTIS OLEH MASYARAKAT DAYAK SIMPAKNG DI DESA SEMANDANG KANAN KECAMATAN SIMPANG DUA KABUPATEN KETAPANG - Persada, Frengky Bagas; Anwari, M Sofwan; Yani, Ahmad (JURNAL HUTAN LESTARI, 2020)
Dayak Simpakng community, which is located in Semandang Kanan Village, Simpang Dua District, Ketapang Regency, is a Dayak community that still preserves ancestral culture for generations. One of their cultures is still utilizing the animals around them as mystical. The purpose of this study is to obtain data of animals species that are used as mystics, the parts used and the meaning of these animals. The method used in this study is a survey method, the selection of respondents was carried out using snowball sampling techniques. Based on the results of interviews with 25 selected respondents obtained 23 species of animals from 19 families which used as a mystic by the Dayak Simpakng community. Some parts that are used as mystical that is the sound, foot in animals and all the body.Keywords: Dayak Simpakng, Ethnozoology, Mystical Animal.